Electron Deficient Monomers that Optimize Nucleation and Enhance the Photocatalytic Redox Activity of Carbon Nitrides. (9th September 2019) - Zhang, Guigang; Liu, Minghui; Heil, Tobias; Zafeiratos, Spiros; Savateev, Aleksandr; Antonietti, Markus; Wang, Xinchen
Abstract: Polymeric carbon nitride (PCN) is usually synthesized from nitrogen‐rich monomers such as cyanamide, melamine, and urea, but is rather disordered in many cases. Now, a new allotrope of carbon nitride with internal heterostructures was obtained by co‐condensation of very electron poor monomers (for example, 5‐amino‐tetrazole and nucleobases) in the presence of mild molten salts (for example, NaCl/KCl) to mediate the polymerization kinetics and thus modulate the local structure, charge carrier properties, and most importantly the HOMO and LUMO levels. Results reveal that the as‐prepared NaK‐PHI‐A material shows excellent photo‐redox activities because of a nanometric hetero‐structure which enhances visible light absorption and promotes charge separation in the different domains. Abstract : Optimale Bedingungen : Eine Copolymerisation mit elektronendefizitären Monomeren in einer Salzschmelze optimiert die Keimbildung, den lokalen Packungsmodus, die Bandstruktur und die optischen Eigenschaften von Kohlenstoffnitridpolymeren. PHI=Poly(heptazinimid).